Fig. 4 in Effects of ocean acidification on phenology and epiphytes of the seagrass Posidonia oceanica at two CO vent systems of Ischia (Italy) Abstract - Mecca, Silvia; Casoli, Edoardo; Ardizzone, Giandomenico; Gambi, Maria Cristina (Zenodo, 2020)
Fig. 4: Percentage of different types of biological apex erosion (Sarpa salpa, sea urchins, and crustaceans) during time at the studied stations and considering only the leaves showing biological erosion. Published as part of Mecca, Silvia, Casoli, Edoardo, Ardizzone, Giandomenico & Gambi, Maria Cristina, 2020, Effects of ocean acidification on phenology and epiphytes of the seagrass Posidonia oceanica at two CO vent systems of Ischia (Italy) Abstract, pp. 70-83 in Mediterranean Marine Science 21 (1) on page 76, DOI:10.12681/mms.20795, http://zenodo.org/record/12551640